Nanodelivery and anticancer effect of a limonoid, nimbolide, in breast and pancreatic cancer cells - Patra A; Satpathy S; Hussain MD (International Journal of Nanomedicine, 2019)
Arjun Patra,1,2 Swaha Satpathy,1,2 Muhammad Delwar Hussain1 1Department of Pharmaceutical and Biomedical Sciences, College of Pharmacy, California Health Sciences University, Clovis, CA, USA; 2Institute of Pharmacy, Guru Ghasidas University, Bilaspur, CG, IndiaCorrespondence: Muhammad Delwar HussainDepartment of Pharmaceutical and Biomedical Sciences, California Health Sciences University, College of Pharmacy, Mailing address: 120 North Clovis Avenue, Clovis, CA 93612, USATel +1 559 369 2715Fax +1 559 473 1487Email dhussain@chsu.eduIntroduction: Nimbolide (Nim), a limonoid obtained from the neem tree, Azadirachta indica, has several pharmacological properties, including anticancer effects in different type of cancers. No drug-delivery system has been reported for enhancing the therapeutic application of this novel hydrophobic molecule.Methods: In the present research, poly(lactic-co-glycolic acid) (PLGA) nanoparticles of Nim (Nim-nano) were formulated by nanoprecipitation, characterized for physicochemical properties, and screened for anticancer potential in breast (MCF-7 and MDA-MB-231) and pancreatic (AsPC-1) cancer cell lines.Results: The Nim-nano had a particle size of 183.73±2.22 nm and 221.20±11.03 nm before and after lyophilization, respectively. Cryoprotectants (mannitol and sucrose) significantly inhibited growth in particle size due to lyophilization. The ζ-potential of the Nim-nano was −22.40±4.40 mV. Drug loading and encapsulation efficiency of Nim-nano were 5.25%±1.12% and 55.67%±12.42%, respectively. The Nim-nano exhibited sustained release of Nim for more than 6 days in PBS (pH 7.4) and showed two- to three-fold enhanced cytotoxicity in breast and pancreatic cancer cell lines compared with free Nim.Conclusion: The Nim-nano formulation has great potential for treatment of cancers, such as pancreatic and breast cancer. Further, the PLGA-polymer surface can be modified by conjugation with polyethylene glycol, receptor-binding ligands (eg, folic acid), and other that which may lead to targeted delivery of Nim in the treatment of cancer.Keywords: nimbolide, PLGA, nanoparticles, breast cancer, pancreatic cancer